2017
DOI: 10.1270/jsbbs.16201
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of the pleiotropic control of leaflet shape and number of seeds per pod by the <i>Ln</i> gene in induced soybean mutants

Abstract: Most soybean cultivars possess broad leaflets; however, a recessive allele on the Ln locus is known to cause the alteration of broad to narrow leaflets. The recessive allele ln has also been considered to increase the number of seeds per pod (NSP) and has the potential to improve yield. Recently, Gm-JAG1 (Glyma20g25000), a gene controlling Ln, has been shown to complement leaf shape and silique length in Arabidopsis mutants. However, whether Gm-JAG1 is responsible for those traits in soybean is not yet known. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 20 publications
2
20
1
2
Order By: Relevance
“…The upper limits for the number of seeds per pod and seed size are determined genetically. However, these two components can still undergo significant changes, thus raising the yield of the genotype (Sayama et al, 2017). These changes in yield can be caused by several factors, such as changes in the environmental elements (relative humidity and air temperature, radiation, precipitation), amount of weeds and pathogens in the crop, agricultural practices, sowing season, maturation group, fertilization (Allen et al, 2017, Cafaro La Menza et al, 2017, among others.…”
Section: Resultsmentioning
confidence: 99%
“…The upper limits for the number of seeds per pod and seed size are determined genetically. However, these two components can still undergo significant changes, thus raising the yield of the genotype (Sayama et al, 2017). These changes in yield can be caused by several factors, such as changes in the environmental elements (relative humidity and air temperature, radiation, precipitation), amount of weeds and pathogens in the crop, agricultural practices, sowing season, maturation group, fertilization (Allen et al, 2017, Cafaro La Menza et al, 2017, among others.…”
Section: Resultsmentioning
confidence: 99%
“…The qSw20-1 is closely linked to the Ln locus; whose recessive allele governs narrow leaflet morphology. Previous studies indicated a relationship between small seed and narrow leaflet phenotypes controlled by the Ln locus ( Dinkins et al 2002 , Jeong et al 2011 , Sayama et al 2017 ). ‘Tachinagaha’ is a narrow leaflet cultivar and the small-seeded ln allele at qSw20-1 was certainly derived from this narrow leaflet parent in the NsT-RIL population ( Supplemental Table 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…The narrow leaflet phenotype, controlled by the Ln locus ( Bernard and Weiss 1973 , Jeong et al 2012 ), is associated with both decreased SSW and increased NOP ( Dinkins et al 2002 , Jeong et al 2011 ). The induced mutant line for the Gm-JAG1 ( Glyma20g25000 ) gene clearly demonstrated the increase in NSP compensated reductions of SSW ( Sayama et al 2017 ) . Therefore, it is likely that SSW and other SYCs are regulated by common loci and share regulatory mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Description of the individual leaflet elongation model Since the node number estimation is the same as the leaf number estimation in soybean, the leaf area for the whole plant may be calculated by adding estimates of the leaf area at each node. Leaf area of each leaflet may be estimated from the leaflet length because the length and width of a leaflet increase symmetrically (Inaba, 1992), while soybean leaflet shape is genetically controlled (Sawada, 1992;Sayama et al, 2017). Individual leaflet elongation rate is highly correlated with the air temperature (Bunce, 1985).…”
Section: Description Of the Node Number Estimation Modelmentioning
confidence: 99%